Infusion of platelet-derived growth factor or basic fibroblast growth factor induces selective glomerular mesangial cell proliferation and matrix accumulation in rats. - Floege, J (1993)
Mesangial cell (MC) proliferation and extracellular matrix expansion are involved in the pathogenesis of glomerulosclerosis and renal failure. In vitro, PDGF and basic fibroblast growth factor (bFGF) regulate MC proliferation and/or matrix production. To elucidate the role of PDGF and bFGF in vivo, equimolar concentrations of recombinant PDGF-BB or bFGF or vehicle were infused intravenously into rats over a 7-d period. Rats were either nonmanipulated ("normals") or had received a subnephritogenic dose of anti-MC antibody ("anti-Thy 1.1 rats") before the infusion period. Glomerular cell proliferation (anti-proliferating cell nuclear antigen immunostaining) on days 2, 4, and 7 was unchanged in vehicle-infused normals or anti-Thy 1.1 rats. PDGF infusion increased glomerular cell proliferation 32-fold in anti-Thy 1.1 rats and an 11-fold in normals on day 2. bFGF increased glomerular cell proliferation fourfold in anti-Thy 1.1 rats but was ineffective in normals. Induction of cell proliferation in all kidneys was limited to the glomerulus. The majority of proliferating cells were identified as MC by double immunolabeling. No significant proteinuria, glomerular leukocyte, or platelet influx developed in any group. Glomerular matrix expansion with increased deposition of type IV collagen, laminin, and fibronectin, as well as upregulated laminin and collagen IV mRNA expression was confined to PDGF-infused anti-Thy 1.1 rats. These results show that PDGF and, to a lesser degree, bFGF are selective MC mitogens in vivo and that previous subclinical injury can enhance this MC response. The data thereby support a role of these cytokines in the pathogenesis of glomerulosclerosis.